Aplikasi Pengaduan Tumpukan Sampah dengan Algoritma Analytical Hierarchy Process (AHP) untuk Menentukan Prioritas Layanan - Ergie Suhendri; Jaroji Jaroji (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
Waste is a waste product of human activities that continues to increase along with the increase in population, activities, and consumption levels. In Bengkalis Sub-district, Bengkalis Regency, there are many waste accumulation points that have not been handled properly, mainly due to the lack of information about the location of waste accumulation. This causes the Bengkalis Regency Environment and Hygiene Agency (DLHK) to have difficulties in managing waste transportation, even though it is carried out every day. There are still many complaints from people who are outside the waste collection point. To overcome this problem, this research aims to develop a mobile application-based garbage pile complaint application focused on the Bengkalis District area. This application is designed to assist DLHK in monitoring environmental cleanliness more effectively. The Analytical Hierarchy Process (AHP) method is used to determine the priority of handling waste complaints, which will be implemented in a web platform to ensure optimal handling. Application development uses a prototype approach to ensure that the resulting application is in accordance with user needs and expectations. With this application, it is hoped that waste management in Bengkalis Regency will become more efficient and responsive to community complaints.